The Effectiveness Of The Combination Neck And Pectoralis Major Muscle Massage To Fluency Of Breast Milk Production On Post Partum Mothers - Ary Oktora Sri Rahayu; Ika Permanasari; Rodiah (Journal of Global Research in Public Health, 2023)
Breastfeeding is the optimal way to meet nutritional needs for infant growth, and is an ideal source of nutrition containing antibody substances to protect babies from various infections, viruses and fungi. Many failures in breastfeeding are caused by several factors, one of which is lack of breast milk production, maternal psychology and nutritional factors. Thus, it requires a method of knowledge about supporting techniques to facilitate breastfeeding in postpartum mothers. One of alternatives to facilitate breastfeeding is to do breast care using a method of combining neck massage and pectoralis major muscle massage. This study to determine the effect of combination of neck and pectoralis major muscle massage on the production of breast milk in postpartum mothers 1-3 days conducted at the Mandah Community Health Center. This Quasy experimental study used pre test and post design with control group. The population was all postpartum mothers at Mandah Community Health Center with a sample size of 20 taken by purposive sampling technique. The instrument was an observation on breast milk production. Data analysis using Mann Whitney testwith ap value of 0.003 <α 0.05, meaning that there was the effect of neck massage and pectoralis major muscle massage on the production of breast milk. There was the effect of the combination of neck massage and pectoralis major muscle massage on the production of breast milk in postpartum mothers 1-3 days. Midwives are expected to be able to disseminate and apply the combination method of neck massage and pectoralis major muscle massage as an alternative option to facilitate breastfeeding for postpartum mothers 1-3 days.